Ver e ser vista: star system e cultura visual nas revistas ilustradas da Sociedade Anônima O Malho - Lopes, Lara (2019)
The beginning of the 20th century was marked by several transformations that contributed to do changes in the aesthetic experience and in sensorial perception of the subjects The press, movies and advertising had a key role in these changes. By inserting the image in the people daily life, they were responsible for changing the sensibility and way of perceiving and behaving in the world. The fusion between different media and the built of a visual culture is one of the main focus of this study. The aim is analyze the illustrated magazines of the Publisher Sociedade Anônima O Malho, in the 1940s, that constantly published photographs of Hollywood actresses on their pages. These images, produced and distributed by the studios themselves, were adapt and re-signified in this editions, in diverse section, according to the graphic and editorial profile of each periodical. Through them we can think about the role of the press in the transmission and keeping the Star System, in the build of images, of the stellar persona and the way these photographs challenged the readers to build their own personal image allied to consumption.